PENGARUH KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP TOP UP STEAM WALLET DI KOTA SURABAYA PADA MASA PANDEMI COVID-19 DAN SESUDAH PANDEMI COVID-19 - Darmawan, Willie (Universitas Widya Kartika Surabaya, 2024)
This research aims to analyze the influence of consumer purchasing decisions on Steam Wallet top ups in the city of Surabaya during the COVID-19 pandemic and after the COVID-19 pandemic. This research uses a quantitative method with an explanatory research type involving 50 respondents who are Steam users who have topped up in Surabaya. Data was collected through questionnaires and analyzed using regression analysis techniques. The research results show that there is a significant influence on consumer purchasing decisions during the COVID-19 pandemic on increasing the number of Steam Wallet top ups. Apart from that, consumer purchasing decisions after the COVID-19 pandemic also showed a significant influence on Steam Wallet top ups. These findings indicate that changes in consumer behavior during and after the COVID-19 pandemic have a direct impact on increasing digital transactions on gaming platforms. This research contributes to understanding the dynamics of consumer behavior in the digital gaming sector during the global health crisis period and provides insights for game platform developers and top up service providers to optimize their marketing strategies in the future.